Pregnancy Outcomes in Uncorrected Ventricular Septal Defect in Tertiary Care Hospital (University Heart Journal, 2025)
Background: Pregnancy in women with uncorrected ventricular septal defect (VSD) poses significant maternal and fetal risks, yet data from low-resource settings remain limited. Aim of the study: To evaluate maternal, obstetric, and neonatal outcomes in pregnancies complicated by uncorrected VSD at a tertiary care hospital.Methods: A retrospective observational study was conducted at Bangladesh Medical University, Dhaka, Bangladesh over a period of July 2022 to June 2024 on 50 pregnant women with echocardiographically confirmed uncorrected VSD. Maternal cardiac status, obstetric complications, and neonatal outcomes were extracted from medical records. VSDs were classified by size and type. Quantitative data were analyzed using SPSS v26, with continuous variables expressed as mean ± SD and categorical variables as frequencies and percentages. Independent t-tests and Chi-square or Fisher’s exact tests were used for comparisons, with p